2020
DOI: 10.2196/18114
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health Impact and Policy Implications of Online Support Group Use for Mental Health in Singapore: Cross-Sectional Survey

Abstract: Background The wide mental health treatment gap continues to pose a global and local public health challenge. Online support groups are on the rise and could be used to complement formal treatment services for mental health. Objective This study aimed to examine the prevalence of online support group use and explore factors associated with the use in the general population using data from a national cross-sectional mental health survey in Singapore. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Social media represents an important proportion of youth's internet use, providing novel and rapidly shifting platforms for communication and content-sharing [2,3]. While social media may positively impact youth by facilitating social connection [4] and providing resources for seeking support [5], there are numerous potential health risks associated with online platforms, including sleep disruption [6], problematic internet use [7], and cyberbullying [8][9][10]. Cyberbullying, defined as the use of electronic communication technologies to bully others [11,12], is widespread among youth, with 59% of US teens reporting that they have experienced online victimization [13].…”
Section: Introductionmentioning
confidence: 99%
“…Social media represents an important proportion of youth's internet use, providing novel and rapidly shifting platforms for communication and content-sharing [2,3]. While social media may positively impact youth by facilitating social connection [4] and providing resources for seeking support [5], there are numerous potential health risks associated with online platforms, including sleep disruption [6], problematic internet use [7], and cyberbullying [8][9][10]. Cyberbullying, defined as the use of electronic communication technologies to bully others [11,12], is widespread among youth, with 59% of US teens reporting that they have experienced online victimization [13].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with marginalized identities who do not have much offline social support may turn to OSGs to compensate for the lack of such resources in their physical environments. In the context of various health conditions, people with mental health disorders are more likely than others to use online support groups [ 13 ]. Moreover, a nationally representative sample of adults indicated that the more they reported having social stigma concerns, the more likely they were to seek online support instead of an in-person support group or traditional treatment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%